PENERAPAN RESTORATIVE JUSTICE MENURUT ASASDUE PROCCES OF LAW DALAM KASUS TINDAK PIDANARINGAN DI INDONESIA DAN PERBANDINGANNYA DIBEBERAPA NEGARA - Fajar Prasetyo, - (2022)
The birth of the idea of restorative justice in minor crimes as a form of alternative settlement carried out through discretion (wisdom) and this alternative is an effort to divert from the criminal justice process outside the formal process to be resolved by deliberation. Then what are included in minor crimes are Article 364 of the Criminal Code, Article 373 of the Criminal Code, Article 379 of the Criminal Code, Article 384 of the Criminal Code, Article 407 Paragraph (1) of the Criminal Code, and Article 482 of the Criminal Code. The problem in this research is related to the existence of obstacles to the application of Restorative Justice and how to apply the solution at each stage of the examination of cases of minor crimes in Indonesia. Coupled a little with how the application of Restorative Justice in Indonesia and its comparison in various countries in law enforcement, especially in the application of Restorative Justice. The research method that the author uses is normative juridical, case approach that has permanent legal force, and comparative approach. Based on the research conducted, the answer is that there are still obstacles in the application of Restorative Justice and ways for the application of Restorative Justice to be implemented properly, namely the need for the Due Process and Crime Control Model, and can find out how the settings for the application of Restorative Justice, especially in dealing with These minor crimes are in Indonesia and in various countries.